2010
DOI: 10.1186/1471-2350-11-56
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphism -119C/G in MYG1 (C12orf10) gene is related to vitiligo susceptibility and Arg4Gln affects mitochondrial entrance of Myg1

Abstract: BackgroundMYG1 (Melanocyte proliferating gene 1, also C12orf10 in human) is a ubiquitous nucleo-mitochondrial protein, involved in early developmental processes and in adult stress/illness conditions. We recently showed that MYG1 mRNA expression is elevated in the skin of vitiligo patients. Our aim was to examine nine known polymorphisms in the MYG1 gene, to investigate their functionality, and to study their association with vitiligo susceptibility.MethodsNine single nucleotide polymorphisms (SNPs) in the MYG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…In the present study, -119G allele was prevalent in vitiligo patients as compared to controls and our results are in line with those of Philips et al [18]. Particularly active cases of vitiligo showed increased frequencies of -119G allele as compared to stable cases suggesting the crucial role of -119G allele in progression of the disease.…”
Section: Snpsupporting
confidence: 95%
See 1 more Smart Citation
“…In the present study, -119G allele was prevalent in vitiligo patients as compared to controls and our results are in line with those of Philips et al [18]. Particularly active cases of vitiligo showed increased frequencies of -119G allele as compared to stable cases suggesting the crucial role of -119G allele in progression of the disease.…”
Section: Snpsupporting
confidence: 95%
“…In addition, MYG1 has been found to be consistently up-regulated in skin biopsies from patients with atopic eczema [17]. Philips et al [18] demonstrated that both -119C/G promoter, and Arg4Gln polymorphisms in the mitochondrial signal of MYG1 have a functional impact on the regulation of the MYG1 gene. Previously, MYG1 promoter polymorphism (-119C/G) was shown to be associated with susceptibility for actively progressing vitiligo in Caucasian population.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, MYG1 is a widely expressed gene shown on the basis of differential hybridization to have elevated expression in melanocytes from vitiligo patients (50). Variation in MYG1 has been found to affect levels of gene expression and to be marginally associated with active vitiligo (51), although this study did not apply appropriate correction for extensive multiple testing. A recent more global analysis of 16,000 transcripts in melanocytes cultured from vitiligo patients versus controls identified a list of 859 differentially expressed genes (52).…”
Section: Spritzmentioning
confidence: 78%
“…In active vitiligo patients, MYG1 expression was increased in both lesional and non-lesional skin, and within the lesional skin of non-active vitiligo patients. These results taken together thus suggests that the -119G allele of the MYG1 promoter sequence is a potential risk-allele for developing vitiligo and for the active state of the disease (Philips et al, 2010).…”
Section: Molecular Genetics-based Studiesmentioning
confidence: 85%
“…Kingo et al (2006) have demonstrated that messenger ribonucleic acid (mRNA) expression of melanocyte proliferating gene 1, or MYG1 (a gene involved in early developmental processes), is elevated in lesional skin of vitiligo patients. Nine SNPs are found within the MYG1 locus for susceptibility to vitiligo (Philips et al, 2010). The MYG1 gene consists of seven exons, culminating as 7.5 kilo-base pair (kb) of DNA on chromosome 12.…”
Section: Molecular Genetics-based Studiesmentioning
confidence: 99%